The implementation of an open-source ERP online solution to support laboratory classes and students assessment in higher education during Covid-19 lockdown - Batista, Carlos (2022)
Trabalho apresentado em 15th anual International Conference of Education, Research and Innovation (ICERI2022), 7-9 novembro 2022, Sevilha, Espanha